Comparative proteomics of Mn(II)‐oxidizing and non‐oxidizing Roseobacter clade bacteria reveal an operative manganese transport system but minimal Mn(II)‐induced expression of manganese oxidation and antioxidant enzymes. Issue 5 (5th May 2014) - Learman, D. R.; Hansel, C. M.
Summary Manganese (Mn) is an essential nutrient and precipitates as minerals with technological and environmental relevance. To gain a proteomic understanding of how bacteria respond to Mn(II) and its connection to oxidation, a comparative examination of the proteomic response of Mn(II)‐oxidizing (Roseobacter sp. AzwK‐3b) and non‐oxidizing (Ruegeria sp. TM1040) alphaproteobacteria was conducted. Both bacteria show an operative Mn(II) transport system. In the absence of Mn(II), both bacteria have higher expression of proteins that were homologous to SitA and SitB, known proteins in the Mn(II) transport system of other alphaproteobacteria. Overall, each bacterium demonstrated a varied response to Mn(II). Ru. TM1040 had a greater number of proteins differentially expressed in response to Mn(II) and also had a group of proteins related to chemotaxis at higher concentrations of Mn(II), suggesting a potential stress response. While both bacteria are able to generate extracellular superoxide and Mn(II) is a known antioxidant, the presence of Mn(II) did not significantly alter the expression of proteins related to antioxidant activity. Heme peroxidases, previously connected to Mn(II) oxidation, were found in the soluble protein extract of R. AzwK‐3b, but only minor differential expression was observed as a function of Mn(II), indicating that their expression was not induced by Mn(II).